HBR Guide to Managing Stress at Work - Harvard Business Review (Harvard Business Review Press, 2014)
The HBR Guide to Managing Stress at Work will help you find a sustainable solution. It will help you reach the goal of getting on an even keel―and staying there. You’ll learn how to : Harness stress so it spurs, not hinders, productivity. Create realistic and manageable routines. Aim for progress, not perfection. Make the case for a flexible schedule. Ease the physical tension of spending too much time at your computer. Renew yourself physically, mentally, and emotionally